Notes on the training of workers in the health sector - Hill Barry; Lenzi Márcia (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1997)
The following notes attempt to contribute to questions on planning, design, and evaluation of training courses for technical personnel in the health sector. The authors analyze and compare trainees' views on their courses and point out issues related to planning, implementation, and some benefits of training for trainees' lives.